Pengukuran Kinerja Perusahaan Menggunakan Metode Malcolm Baldrige (Studi Kasus: Divisi Assembly PT. XYZ) - Erwin Octau Herawan; Fathurohman; Aina Nindiani (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This study aims to measure the performance of a shoe company, namely PT. XYZ, which is represented through the Assembly Division. The analytical method uses Malcolm Baldrige, with the type of research used is descriptive qualitative. The results of the study show that the performance measurement results in the Assembly Division are at the Average level with the title of Emerging Industry Leader. Based on the results of these measurements, it was found that some improvements were still needed, especially on the criteria that affect the financial results and the company's market as a whole. The Assembly Division plays a vital role in creating a product that will be sold to the market. Vertical and horizontal integration is urgently needed by the Assembly Division, in order to positively and sustainably improve performance for all other divisions. The implications of this research are expected to help the assembly division in particular to improve its performance. In addition, this research can be used as a benchmark for other divisions or PT XYZ as a whole to measure performance using the Malcolm Baldrige method, so that equity and company levels can be clearly identified